Continuous Hydrogenation: Triphasic System Optimization at Kilo Lab Scale Using a Slurry Solution - Salique, Florian; Musina, Ancuta; Winter, Marc; Yann, Nedelec; Roth, Philippe M. C. (Frontiers in Chemical Engineering, 2021)
Despite their widespread use in the chemical industries, hydrogenation reactions remain challenging. Indeed, the nature of reagents and catalysts induce intrinsic safety challenges, in addition to demanding process development involving a 3-phase system. Here, to address common issues, we describe a successful process intensification study using a meso-scale flow reactor applied to a hydrogenation reaction of ethyl cinnamate at kilo lab scale with heterogeneous catalysis. This method relies on the continuous pumping of a catalyst slurry, delivering fresh catalyst through a structured flow reactor in a continuous fashion and a throughput up to 54.7 g/h, complete conversion and yields up to 99% . This article describes the screening of equipment, reactions conditions and uses statistical analysis methods (Monte Carlo /DoE) to improve the system further and to draw conclusions on the key influential parameters (temperature and residence time).